Brasilonema lichenoides sp. nov. and Chroococcidiopsis lichenoides sp. nov. (Cyanobacteria): two novel cyanobacterial constituents isolated from a tripartite lichen of headstones. Issue 2 (21st February 2018) - Villanueva, Chelsea D.; Hašler, Petr; Dvořák, Petr; Poulíčková, Aloisie; Casamatta, Dale A.
Abstract : Cyanolichens are an assemblage of fungi and cyanobacteria from diverse, cosmopolitan habitats. Typically composed of a single species of cyanobacterium, with or without another eukaryotic alga, here we present two novel cyanobionts isolated from an undescribed tripartite lichen. This endolithic lichen was isolated from a granite cemetery tombstone from Jacksonville, FL, and contains two potentially nitrogen‐fixing cyanobionts. Employing a total evidence approach, we characterized the cyanobionts using molecular (the 16S rDNA and ITS gene region), morphological, and ecological data. Phylogenetic analyses revealed two novel taxa: Brasilonema lichenoides and Chroococcidiopsis lichenoides, both of which fell within well‐supported clades. To our knowledge, this represents the first instance of a tripartite lichen with two cyanobacterial and no eukaryotic members. These types of lichens may well represent an unexplored reservoir of cyanobacterial diversity. The specific epithets are proposed under the provisions of the International Code of Nomenclature for algae, fungi, and plants.